GIS-BASED GROUNDWATER VULNERABILITY MAPPING AND CONFLICT AREAS OF REGIONAL SPATIAL PLANNING IN GERMANY - Vieira Tani, Laura; Lehné, Rouwen J.; Hoppe, Andreas (Águas Subterrâneas, 2019)
To aide in land use decision-making for the protection of groundwater quality, many countries have consider to apply the aquifer vulnerability maps. A detailed intrinsic groundwater vulnerability assessment was developed by applying the standard “DRASTIC” and “GLA” methods, integrated to a Geographical Information System (GIS), to analyze a variety of hydrogeological settings, besides the land use and land cover data assessment in a small river basin localized in the Rhine-Main plains, central part of Germany. Thus, the superposition of mapped layers showed some relevant conflicts among the areas with the higher index values for groundwater vulnerability and the pre-defined areas by the governmental regional spatial planning. In an overall analysis, the major part of these high groundwater vulnerability areas were not matching the groundwater protection zones. Beyond that, a significant part of the groundwater protection zones was not intersected with the groundwater recharge zones, but matching, essentially, the areas mapped as forest and green lands. However, most of potential pollution sources related to the land use in this catchment (mining, industries, agriculture, settlements etc.) were placed along the river’s banks, but in a relative distance from the groundwater protection zones and the most vulnerable areas.